Understanding metabolic perturbations in palm wine during storage using multi-platform metabolomics. (1st February 2022) - Doddipalla, Raju; Rendedula, Deviprasad; Ganneru, Sireesha; Kaliyaperumal, Muralidharan; Mudiam, Mohana Krishna Reddy
Abstract: The metabolic perturbations in palm wine under five (0, 12, 24, 48, 72 h) storage intervals was studied using NMR and LC-HRMS. From 100 (25 from NMR and 75 from LC-HRMS) identified metabolites, 9 and 10 from NMR and LC- HRMS were identified as differential metabolites on storage which includes sugars, organic acids, polyols, and amino acids. The sugars and organic acids were significantly altered upon palm wine storage as organic acids dependent on sugars for a carbon source in energy metabolism. This also confirms from the change of pH from 4.35 to 3.26 during storage. The MetPA analysis revealed that, five metabolic pathways (starch and sucrose metabolism, pyruvate metabolism, sulphur metabolism, and galactose metabolism from NMR; TCA cycle and galactose metabolism from LC- HRMS) were altered during palm wine storage. In conclusion, the study has shown the potential of two complementary analytical tools (NMR & LC-HRMS) in identifying a large pool of metabolites and thus, reveals the alterations in palm wine during successive fermentation. The present study finds application in exploring its sensory quality for public health and for commercialization. Further, it illustrats the role of organic acids and sugars in the fermentation of palm wine during storage. Highlights: Metabolic perturbations in palm wine on storage were studied. Palm wine storage altered significant levels of organic acids and sugars. MetPA results showed perturbations in five metabolic pathways. Multi-platform metabolomics able to identify the large number of metabolites.